The Impact of WhatsApp Chatbot-Based Educational Intervention on Nutritional Literacy of Pregnant Women: A Quasi-Experimental Study in the Cot Seumeureng Community Health Center Work Area - Zakiyah Zakiyah; Anggi Maulida Sari (Media Publikasi Cendekia Indonesia, 2026)
Ensuring optimal nutritional intake during pregnancy is fundamental to supporting healthy fetal growth and development. Consequently, enhancing the nutritional literacy of pregnant women is a critical public health objective to prevent adverse outcomes such as stunting and maternal anemia. This study aimed to evaluate the efficacy of a WhatsApp chatbot-based educational intervention in improving pregnant women's nutritional literacy. A quasi-experimental study with a pre-post test control-group design was conducted at the Cot Seumeureng Community Health Center in West Aceh. Using purposive sampling, 84 pregnant women were enrolled and divided into an intervention group (n=42) and a control group (n=42). The intervention group received structured nutrition education delivered via a WhatsApp chatbot over a four-week period, whereas the control group received standard antenatal services. Data were collected using a modified and validated Nutrition Literacy Assessment Instrument for Pregnant Women (NLAI-P) and analyzed using Paired and Independent Sample T-Tests. The findings indicated a substantial increase in the mean nutritional literacy scores of the intervention group, rising from 12.05 to 19.19. In contrast, the control group’s scores remained relatively stagnant, moving from 13.05 to 13.33. The Independent Sample T-Test confirmed a statistically significant difference in post-test outcomes between the two groups (t=−7.626;p=0.000), demonstrating the superior impact of the digital intervention. A WhatsApp chatbot-based educational intervention is a highly effective, accessible, and innovative modality for significantly enhancing maternal nutritional literacy.